2002
DOI: 10.1093/jexbot/53.368.473
|View full text |Cite
|
Sign up to set email alerts
|

Leaf initiation and development in soybean under phosphorus stress

Abstract: Experiments investigated changes in leaf development in young soybean plants progressing into P stress. The apical meristem and leaf structure were examined anatomically to evaluate the involvement of cell division and cell expansion in the restriction of leaf number and individual leaf size. Seedlings were deprived of P for 32 d following germination. Leaf initiation rates declined noticeably after about 2 weeks, even though the apical dome was of similar size and had a similar number of cells as controls. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
2
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 14 publications
7
59
2
2
Order By: Relevance
“…This has also been confirmed in brassicas (Hammond et al 2009) and demonstrated for production of lateral roots (Zhu and Lynch 2004). Leaf growth depression under phosphorus deficiency is also well documented (Chiera et al 2002, Assuero et al 2004, Kavanová et al 2006.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…This has also been confirmed in brassicas (Hammond et al 2009) and demonstrated for production of lateral roots (Zhu and Lynch 2004). Leaf growth depression under phosphorus deficiency is also well documented (Chiera et al 2002, Assuero et al 2004, Kavanová et al 2006.…”
Section: Resultsmentioning
confidence: 62%
“…3B). Chiera et al (2002) showed that the cell size and thickness of epidermal cell were decreased under phosphorus deficient conditions in soybean leaf. In +P plant, cuticle was thinner than that of -P plant.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most striking effect of P deficiency is a reduction in leaf growth both in terms of leaf number and individual leaf size (Lynch et al, 1991;Chiera et al, 2002). Leaf initiation at the shoot meristem and its lateral expansion are controlled by the activities of cell division (Chiera et al, 2002;Assuero et al, 2004).…”
Section: Maintenance Of Cell-division and Epidermal Cell Expansionmentioning
confidence: 99%
“…Leaf initiation at the shoot meristem and its lateral expansion are controlled by the activities of cell division (Chiera et al, 2002;Assuero et al, 2004). Pi was reported to play a significant role in cell division activities (Sano et al, 1999).…”
Section: Maintenance Of Cell-division and Epidermal Cell Expansionmentioning
confidence: 99%
See 1 more Smart Citation